YY1/ITGA3 pathway may affect trophoblastic cells migration and invasion ability. (September 2022) - Wang, Yanqing; Yang, Dongyong; Zhu, Ronghui; Dai, Fangfang; Yuan, Mengqin; Zhang, Li; Zheng, Yajing; Liu, Shiyi; Yang, Xiao; Cheng, Yanxiang
Abstract: Recurrent spontaneous abortion (RSA) is a disturbing pregnancy disorder experienced by ~2.5% of women attempting to conceive. The pathogenesis of RSA is still unclear. Previous findings revealed that transcription factor YIN-YANG 1(YY1) was related to the pathogenesis of RSA by influence trophoblastic cell invasion ability. Present study aimed to investigate more specific molecular mechanism of YY1 playing in trophoblastic cells. In our research, RNA-seq and Chip-seq were used to find significant changed genes between si-YY1(Knock down of YY1) HTR-8/SVneo cells(n = 3) and HTR-8/SVneo cells(n = 3). Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis results suggested that Integrins related pathway maybe necessary to biological functions of trophoblastic cells. Chip-seq dataset analysis results predict YY1 can regulate ITGA3/7 expression by binding to the promoter region of ITGA3/7. Furthermore, results from chip experiment, RT-PCR, Dual-luciferase reporter gene assay showed that YY1 was able to bind to the promoter region of ITGA3 and regulate ITGA3 mRNA and protein expression. However, ITGA7 could not be significant influenced by YY1. Besides, gene silencing experiment, Western blot and Immunofluorescence assay confirmed that both YY1 and ITGA3 can accelerate phosphorylation focal adhesion kinase and affect cytoskeleton formation in HTR-8/SVneo cells. In conclusion, YY1/ITGA3 play a critical role in trophoblast invasion ability by regulating cytoskeleton formation. Highlights: YY1 as a transcription factor can transcriptionally regulate the expression of ITGA3. YY1 and ITGA3 can accelerate p-FAK level and affect cell skeletal formation of HTR-8/SVneo cells. YY1/ITGA3 may be involved in the pathogenesis of RSA by decreasing cell skeletal formation.